1990
DOI: 10.5980/jpnjurol1989.81.1217
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factor for Prostate Cancer

Abstract: The study of prognostic factors in patients with prostate cancer (Pca) may be of value in understanding the natural history of the disease and may also assist in planning and analyzing the results of clinical trials. Moreover some information through this study would be beneficial to assessing the prognosis and decision of better therapy form of individual patients. The significance of items studied was evaluated from the two view points, survival rate and Pca death rate. Stage, pathological differentiation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, the above result indicates a better survival for subjects examined by M S, but not for the survival o f Pea patients detected by M S. Therefore, we analyzed the possibility o f a self-selection bias by evaluating the clinical data o f the Pea patients. We have reported that ESR in stage B and gait disturbance in all stages reflect the general condition o f patients with Pea [ 18]. In stage B and D patients there was a significant difference between M S and the controls (p < 0.05: tables 5, 6).…”
Section: Self-selection Biasmentioning
confidence: 83%
“…However, the above result indicates a better survival for subjects examined by M S, but not for the survival o f Pea patients detected by M S. Therefore, we analyzed the possibility o f a self-selection bias by evaluating the clinical data o f the Pea patients. We have reported that ESR in stage B and gait disturbance in all stages reflect the general condition o f patients with Pea [ 18]. In stage B and D patients there was a significant difference between M S and the controls (p < 0.05: tables 5, 6).…”
Section: Self-selection Biasmentioning
confidence: 83%
“…The latter was typified by having a more advanced stage distribution and (22) 3 (4) 8 (10) 12 (5) 20 (9) 12 ( younger mean age. These data suggest that the patients in the RPCI-2 group were self-or physicianreferred to RPCI because of the advanced nature of their disease or their younger age.…”
Section: Discussionmentioning
confidence: 99%
“…Although chemical synthesis and enzymological studies are only tersely disclosed, a number of in vivo studies have been published. ONO rats (21,22). Clinical studies in humans are reportedly underway, although recent results are not available (23,24).…”
Section: Dihydrotestosterone (Dht)mentioning
confidence: 99%